Wind resource assessment in heterogeneous terrain. (13th April 2017) - Vanderwel, C.; Placidi, M.; Ganapathisubramani, B.
Abstract : High-resolution particle image velocimetry data obtained in rough-wall boundary layer experiments are re-analysed to examine the influence of surface roughness heterogeneities on wind resource. Two different types of heterogeneities are examined: (i) surfaces with repeating roughness units of the order of the boundary layer thickness (Placidi & Ganapathisubramani. 2015 J. Fluid Mech. 782, 541–566. (doi:10.1017/jfm.2015.552 )) and (ii) surfaces with streamwise-aligned elevated strips that mimic adjacent hills and valleys (Vanderwel & Ganapathisubramani. 2015 J. Fluid Mech. 774, 1–12. (doi:10.1017/jfm.2015.228 )). For the first case, the data show that the power extraction potential is highly dependent on the surface morphology with a variation of up to 20% in the available wind resource across the different surfaces examined. A strong correlation is shown to exist between the frontal and plan solidities of the rough surfaces and the equivalent wind speed, and hence the wind resource potential. These differences are also found in profiles of and (where U is the streamwise velocity), which act as proxies for thrust and power output. For the second case, the secondary flows that cause low- and high-momentum pathways when the spacing between adjacent hills is beyond a critical value result in significant variations in wind resource availability. Contour maps of and show a large difference in thrust and power potential (over 50%) between hills and valleys (at a fixed vertical height). These variations do not seem to be present when adjacent hills are close to each other (i.e. when the spacing is much less than the boundary layer thickness). The variance in thrust and power also appears to be significant in the presence of secondary flows. Finally, there are substantial differences in the dispersive and turbulent stresses across the terrain, which could lead to variable fatigue life depending on the placement of the turbines within such heterogeneous terrain. Overall, these results indicate the importance of accounting for heterogeneous terrain when siting individual turbines and wind farms. This article is part of the themed issue 'Wind energy in complex terrains'.